Strategi Pengembangan Pariwisata Dalam Mengoptimalkan Pendapatan Asli Daerah Di Dinas Kebudayaan dan Pariwisata Kota Surakarta - Partiwi, Widya; Winarti; Suranto, Joko (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The Surakarta City Culture and Tourism Office is a government body which has the taskof formulating policies, carrying out government affairs and public services, developingand implementing as well as monitoring, evaluating and reporting all matters relatingto culture, traditional arts, history, cultural heritage, museums, tourism destinations,tourism marketing, creative economy development through the use and protection ofintellectual property rights, and development of tourism and creative economy resources.The city of Surakarta or the city of Solo, known by its slogan as